Cytomegalovirus infection in a volunteer blood donor population. - Kane, R C (1975)
Among 223 volunteer blood donors who were studied for evidence of cytomegalovirus (CMV) infection, 58 percent had complement-fixing antibody and 59 percent had indirect hemagglutinating antibody to CMV. No virus was isolated from any donor's washed leukocytes or leukocyte-rich plasma in fibroblast monolayer culture. In seven asymptomatic donors (3 percent), CMV was recovered from urine cultures obtained at the time of blood donation. However, at the time of reexamination, viruria was no longer present and serum antibody titers had not changed. In the three patients studied who received blood from three of the cytomegaloviruric donors, serological evidence of CMV infection developed (fourfold or greater indirect hemagglutinating antibody rise), and one recipient also developed cytomegaloviruria; no illnesses was associated with these infections. Further study is needed to establish that the detection of viruria in donors may identify potentially infective blood.